2021
DOI: 10.1002/jbt.22825
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and cytotoxic evaluation of latroeggtoxin‐VI against PC12 cells

Abstract: Latroeggtoxin‐VI (LETX‐VI) is a peptide neurotoxin discovered from Latrodectus tredecimguttatus eggs. In the current study, the action features of the neurotoxin on PC12 cells were systematically investigated. LETX‐VI could promote dopamine release from PC12 cells in the absence and presence of Ca2+, involving an even more complex action mechanism in the presence of Ca2+ and when the treatment time was longer. Although LETX‐VI enchanced the autophagy and secretion activity in PC 12 cells, it showed no remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…After 50 µM BAPTA‐AM was employed to chelate cytosolic Ca 2+ , LETX‐VI treatment resulted in a certain increase in total dopamine but had no obvious affect on the released dopamine level, irrespective of the addition of extracellular Ca 2+ or not. These observations demonstrate that the promoting effect of LETX‐VI on dopamine release needs the mediation of cytosolic Ca 2+ and suggest that LETX‐VI may also enhance dopamine synthesis in a Ca 2+ ‐independent way (Tang et al 2021a).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…After 50 µM BAPTA‐AM was employed to chelate cytosolic Ca 2+ , LETX‐VI treatment resulted in a certain increase in total dopamine but had no obvious affect on the released dopamine level, irrespective of the addition of extracellular Ca 2+ or not. These observations demonstrate that the promoting effect of LETX‐VI on dopamine release needs the mediation of cytosolic Ca 2+ and suggest that LETX‐VI may also enhance dopamine synthesis in a Ca 2+ ‐independent way (Tang et al 2021a).…”
Section: Resultsmentioning
confidence: 89%
“…In the transcriptome analysis of the L.tredecimguttatus eggs, Xu et al found a series of genes that encode proteinaceous toxins, two of which were named latroeggtoxin-V and latroeggtoxin-VI, respectively (Xu and Wang 2016). Latroeggtoxin-V was shown to selectively inhibit breast cancer cell lines MDA-MB-231 by affecting the activity of Na + /K + -ATPase (Xu et al 2018) Latroeggtoxin-VI (LETX-VI) can increase the levels of total and released dopamine in PC12 cells, which is influenced by extracellular Ca 2+ and, however, the exact underlying molecular mechanism has not been fully clear (Tang et al 2021a).…”
Section: Introductionmentioning
confidence: 99%